2016
DOI: 10.1002/adma.201604600
|View full text |Cite
|
Sign up to set email alerts
|

From Micro to Macro: The Hierarchical Design in a Micropatterned Scaffold for Cell Assembling and Transplantation

Abstract: A microwell-patterned membranous scaffold that integrates nano- and microscale topographical characteristics based on polyurethane is fabricated for transplanting syngeneic islets and allogeneic mesenchymal stem cells into diabetic rodents. The scaffold effectively allows for assembling of single cells/microtissues, enables the transplantation of cells with spatial control, and improves the transplant's engraftment efficacy in vivo for treating diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…In comparison, cell clumping and central necrosis were observed in the islets dispersed in tissue culture plates. This is probably because the absence of ECM lead to the necrosis of the dispersed islets leading to poor islet survival and transplantation failure . In addition, islets were also encapsulated using a positively charged P‐Alg/PEI hydrogel, but the islets were all dead after 24 h culture, probably due to the excess positive charges in the hydrogel could damage the cells (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, cell clumping and central necrosis were observed in the islets dispersed in tissue culture plates. This is probably because the absence of ECM lead to the necrosis of the dispersed islets leading to poor islet survival and transplantation failure . In addition, islets were also encapsulated using a positively charged P‐Alg/PEI hydrogel, but the islets were all dead after 24 h culture, probably due to the excess positive charges in the hydrogel could damage the cells (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The nanofibrous material allows proper diffusion of nutrients across it and assists in cell adhesion. The combination of 3D spheroids with the electrospun fibers showed improved cell functions in rodent models . A recent study has demonstrated that the sophisticated double 3D strategy could increase the efficiency of implants even in the absence of bioactive molecules.…”
Section: Recent Advancesmentioning
confidence: 99%
“…However, most efforts are centered on static patterns. [ 6,7 ] Inspired by dynamic, tissue‐specific microenvironments in vivo, the use of dynamic cell culture platforms to create synthetic microenvironments in vitro has become an attractive means to direct active changes in cellular functionality and to replicate the dynamic complexity of native tissues. [ 8,9,10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] 3D cell aggregates can closely resemble the native configuration of NSCs in vivo, which allows for direct cell–cell signaling and cell–matrix interactions when compared to 2D culture substrates or 3D scaffolds. [ 7,18 ] Several studies have induced NSC aggregation using a cell spheroid technique. However, the generation of conventional cell spheroids typically involves a complicated culturing process, which has been criticized for being sensitive to cell culture conditions, and often results in inconsistently differentiated cells, even between experimental trials.…”
Section: Introductionmentioning
confidence: 99%